EFFECT OF VARIOUS SUBSTRATES IN NON-CIRCULATING HYDROPONIC SYSTEMS AND SOIL MEDIA ON THE GROWTH OF Gynura procumbens - Hanik Faizah; Ikhlasotul Fawaidah; Najmatul Millah; Ninik Fadhillah; Muh. Ma’arif (Universitas Negeri Medan, 2020)
The limitations of conventional soil cultivation in producing medicinal plants emerge an interest in searching various alternative cultivation systems, one of which is the hydroponic system. This study aimed to investigate the effect of various substrates in non-circulating hydroponic systems and soil media on the growth of Gynura procumbens. Non-circulating hydroponic cultivation of Gynura procumbens was carried out using stem cuttings. The stem cuttings were transferred to each net pot containing substrates such as rockwool, tree ferns fiber, and sawdust. The net pots were then placed in a tray comprising AB mix 6 ml/L of water. The lower 2-cm-portion of the net pots was immersed in a nutrient solution. Whereas in the conventional soil cultivation, the stem cuttings were transferred to the polybags containing soil media: compost (1: 1). After 28 days of cultivation, the plant growths were measured. The results showed that the use of various substrates in non-circulating hydroponics increased plant growth compared to conventional soil cultivation. Rockwool treatment obtained the highest number of leaves (14,833 ± 5,269 strands), number of roots (20,333 ± 6,121 stands), fresh weight (1.34 ± 0.511 g) and dry weight (0.088 ± 0.031 g).